The Polarization Multiplexing Image with a Single Diffractive Optical Element - Jiazhou Wang; Hui Pang; Axiu Cao; Man Zhang; Ruifeng Kan; Song Hu; Lifang Shi; Qiling Deng (IEEE Photonics Journal)
The diffractive optical element (DOE) can modulate the light to image in a fixed distance. However, when the wavelength of the light is single and fixed, the imaging is single. In this paper, we proposed a novel architecture to solve this problem. The birefringent material is used as the substrate of the DOE, and the polarization modulation is added in the design of the DOE. The two orthogonally linear polarized lights with the same wavelength modulated by the DOE image differently at the same distance. The imaging of incident light with different polarization is simulated, and the diffraction efficiency and the uniformity are also calculated to demonstrate the validity of this mew method.